Seasonal patterns of reproduction of Norops humilis (Sauria: Iguanidae) in Costa Rica - Guyer, Craig (1986)
Monthly samples of Norops humilis were collected from Dec. 1973 through Dec. 1974. Dissection of sacrificed animals revealed that females reach sexual maturity at a body length of 32 mm, whereas males reach maturity at lengths as low as 25 mm. Sexually mature lizards of both sexes were found throughout the year, confirming that reproduction occurs year-round. However, a gap in the occurrence of juveniles occurred during the months of Feb. and Mar. 1974, indicating that recruitment of juveniles was not constant throughout the year. Contrary to previous data on N. humilis from Costa Rica, lizards were more abundant during the dry season (Jan. - May) than during the wet season.